Designing the training program for forest guard - an action research approach - Mengga, Anak Mikui. (1998)
Forest C'~partment, Sarawak has onc thousand nine hundred and seventy four employees. More I'lan halves of the total number of the employees are Forest Guards. They are responsible for fiel.:! works such !b logging supervision, royalty assessment and enforcement of forest laws. They playa very important role in determining the success of the implementation of thl: organizational functions. Therefore, it is critical for the organization to provide proper, systematic and up to date training 10 mcet the organizational requirements. Transformation of the Forest Department fro'll public agency to a corporatised organisation necessitates the Forest Guards to go for further trainillg to enhance their competency in perform::tg thcir functions effectively. Due to the changes in the functions, work processes and new technology adopted by the organisation, new knowledgc and skills are requircd. Training is identificd as one way of reducing incompetence. I .. 'Jrder for the training to be effective in giving the relevant competency, the designing of the training program play~ a critical role. To start with, there is a ;·ieed to review the current training program to determine its effectiveness to meet current and future needs. If it is found to be inadequate, then dcsigning a new training orogram is necessary.In this study, action research methodology is used to determine whether the current training program is still etTective or not and also to design a new training program. Six trainers from Forest Training School 'Sarawak and the researcher forms the core action research group in this study. Information and data was collected through in~ervie""s and group discussions. The respondents for the interviews were mainly key personnel from within the organisatio!1 and out~ide agellcies such as Ir.tcmatio:lal Tropicai Timber Organisa!ior., Sarawak Timber Association and others. The study indicated that the cum:nt Forest Guard training program is not adequate to m.:et the current and future needs, as it is outdakd, generalizing in nature, lacking specialization and did not include management subjects. The lack of competency in designing the program is identified as a major contributor for the ::>oor versatility in the curriculum. To remedy the problem, the trainers did a hand on exercise on designing a training program through action le!lrning. The trainers, through action learning acquire the knowledge and skill effectively and even manage to compile a manual on the process of designing a training program. The action group member:; through the process of acticn research cycles managed to desiEn a training progr:tm or. a Introductory to Park and Wildlife Management" and implement the pilot training program s:Jccessfully. Base on this study, action research is found te be applical)le for developing and implementing the training program. Thus, action research is recommended to be continually adopted forfsuch purpose in the future.